2008
DOI: 10.1029/2008jc004829
|View full text |Cite
|
Sign up to set email alerts
|

Ice‐Tethered Profiler observations of the double‐diffusive staircase in the Canada Basin thermocline

Abstract: À2 , only about one tenth of the estimated mean surface mixed layer heat flux to the sea ice. It is thus concluded that the vertical transport of heat from the Atlantic Water in the central basin is unlikely to have a significant impact to the Canada Basin ocean surface heat budget. Icebreaker conductivity-temperature-depth data from the Beaufort Gyre Freshwater Experiment show that the staircase is absent at the basin periphery. Turbulent mixing that presumably disrupts the staircase might drive greater flux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
290
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(319 citation statements)
references
References 42 publications
27
290
2
Order By: Relevance
“…Furthermore, the field observations of Padman & Dillon (1987) and Timmermans et al (2008) have shown a close agreement between F mol T and the F T predicted by different laboratorybased flux laws. However, we are not aware of any study that has definitively shown the fluxes to be molecular, with the exception of the experiments of Shirtcliffe (1973) using a salt-sugar interface (τ ≈ 0.33).…”
Section: Simulations Of a Double-diffusive Interfacesupporting
confidence: 60%
“…Furthermore, the field observations of Padman & Dillon (1987) and Timmermans et al (2008) have shown a close agreement between F mol T and the F T predicted by different laboratorybased flux laws. However, we are not aware of any study that has definitively shown the fluxes to be molecular, with the exception of the experiments of Shirtcliffe (1973) using a salt-sugar interface (τ ≈ 0.33).…”
Section: Simulations Of a Double-diffusive Interfacesupporting
confidence: 60%
“…The Arctic Ocean is a quiescent environment with turbulence levels close to the limits of measurement (RainCorresponding author: Ilker FER, ilker.fer@gfi.uib.no ville and Winsor, 2008). In the absence of enhanced levels of mixing due to episodic shear events or mesoscale eddies, diffusive layer fluxes dominate over turbulent fluxes (Padman and Dillon, 1989;Timmermans et al, 2008). Consistent with a quiescent Arctic interior, recent numerical studies suggest that the observed AW layer circulation in the Arctic Ocean requires low vertical mixing (Zhang and Steele, 2007).…”
Section: Introductionmentioning
confidence: 87%
“…Estimating the vertical fluxes through such staircases is important, in particular in the Arctic Ocean, where double-diffusive heat transport to the overlying ice needs to be quantified [Timmermans et al, 2008;Turner, 2010].…”
Section: Introductionmentioning
confidence: 99%